2013
DOI: 10.1016/j.bbi.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Serum and gene expression profile of cytokines in first-episode psychosis

Abstract: Highlight► First-episode psychosis is characterised by a pro-inflammatory state supported partly by activation of leukocytes. Stress contributes to this pro-inflammatory state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
125
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(141 citation statements)
references
References 41 publications
(23 reference statements)
13
125
3
Order By: Relevance
“…The presence of increased levels of IL-6, TNF-α and IL-1β in individuals with first-episode psychosis is consistently reported across several different studies [18,19,20,21,22]. Indeed, abnormal levels of other inflammatory markers have also been reported in first-episode psychosis, including increased levels of IL-12, IL-1α and TGF-β, and decreased levels of IL-5 [18,23,24,25]. However, these latter findings come from single studies which have not been replicated yet.…”
Section: Markers Of Inflammation In First-episode Psychosismentioning
confidence: 90%
“…The presence of increased levels of IL-6, TNF-α and IL-1β in individuals with first-episode psychosis is consistently reported across several different studies [18,19,20,21,22]. Indeed, abnormal levels of other inflammatory markers have also been reported in first-episode psychosis, including increased levels of IL-12, IL-1α and TGF-β, and decreased levels of IL-5 [18,23,24,25]. However, these latter findings come from single studies which have not been replicated yet.…”
Section: Markers Of Inflammation In First-episode Psychosismentioning
confidence: 90%
“…We only have data representing current white blood cells parameters and have no information regarding presence of past hematological abnormalities. White blood cells parameters may also result from other factors, which could not be included in the analysis, such as detailed inflammatory status of individuals (e.g., levels of other inflammatory biomarkers, subtypes of lymphocytes), exposure to ionizing radiation [26], nutritional status [27,28], lifestyle [29], duration of disease [13,[30][31][32], etc. which also may have a significant impact on white blood cells parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies carried out in FEP either have excluded the overweight individuals [7,20,23] from the analysis or have not considered the BMI in the analysis [6,18] because the result was similar between patients and controls. Regarding the two articles that did not consider the effect of the BMI, Di Nicola et al [6] and Noto et al [18] observed that IL-6, TNF-α, and IL-8 were higher in patients than in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the two articles that did not consider the effect of the BMI, Di Nicola et al [6] and Noto et al [18] observed that IL-6, TNF-α, and IL-8 were higher in patients than in healthy volunteers. On the other hand, regarding the three studies which excluded overweight individuals from the analysis, Ding et al [7] found that IL-6 and IL-17 were increased in patients when compared to controls, Song et al [23] found that IL-6, TNF-α, and IL-1β were elevated in patients compared to healthy volunteers, and [20] observed that IL-6 and IL-2 were higher in patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation